166k views
4 votes
Y = x - 2 and y=-2x +7

2 Answers

4 votes

Answer:

x = 3 , y = 1

Explanation:

Solve the following system:

{y = x - 2 | (equation 1)

y = 7 - 2 x | (equation 2)

Express the system in standard form:

{-x + y = -2 | (equation 1)

2 x + y = 7 | (equation 2)

Swap equation 1 with equation 2:

{2 x + y = 7 | (equation 1)

-x + y = -2 | (equation 2)

Add 1/2 × (equation 1) to equation 2:

{2 x + y = 7 | (equation 1)

0 x+(3 y)/2 = 3/2 | (equation 2)

Multiply equation 2 by 2/3:

{2 x + y = 7 | (equation 1)

0 x+y = 1 | (equation 2)

Subtract equation 2 from equation 1:

{2 x+0 y = 6 | (equation 1)

0 x+y = 1 | (equation 2)

Divide equation 1 by 2:

{x+0 y = 3 | (equation 1)

0 x+y = 1 | (equation 2)

Collect results:

Answer: {x = 3 , y = 1

User Djnz
by
6.2k points
2 votes


\huge\boxed{\boxed{\bold{(3, 1)}}}


\hrulefill

I'm assuming you need to find the solution to this system of equations (where the lines intersect).

We can use the substitution method to solve this system. Take the value of
y from the second equation and substitute it into the first:


-2x+7=x-2

Add
2x to both sides of the new equation:


7=3x-2

Now add
2 to both sides of the equation:


9=3x

Divide both sides by
3:


\boxed{3}=x

Now let's solve for
y by substituting the known value of
x into the first equation:


y=3-2

Simplify using subtraction:


y=\boxed{1}

This means our solution is:


\large\boxed{(3, 1)}

User PolGraphic
by
5.7k points